Pengaruh Pemberian Ekstrak Biji Kopi Robusta Lampung (Coffea canephora) terhadap Nilai Elevated Plus Maze (EPM) Kecemasan Tikus Putih Jantan (Rattus novergicus) Galur Sprague dawley yang Diinduksi Monosodium Glutamat (MSG) - Eca Cania B; Adillah Afrilia Syahwina Pado; Anggraeni Janar Wulan (Medula, 2021)
Anxiety can be triggered by consuming MSG through the mechanism of oxidative stress. Lampung Robusta coffee bean extract contains polyphenols, given as an antioxidant and neuroprotective. To know the effect of the giving of Lampung Robusta Coffee Bean extract (Caffea canephora) to the value of Elevated Pus Maze (EPM) Anxiety of Male White Rats (Rattus novergicus) Sprague Dawley strain induced by Monosodium Glutamate (MSG). Experimental research with Posttest Only Control Group Design. This study used 25 Sprague Dawley (Rattus norvegicus) male rats randomly selected and divided into 5 groups namely, K1 (negative control), K2 (MSG 2g / kgBB / day), P1 (MSG 2g / kgBB / day + coffee 0.5mg / ml), P2 (MSG2g / kgBB / day + coffee 1mg / ml) and P3 (MSG2g / kgBB / day + coffee 2mg / ml). The mean duration (seconds) on the open arm was K1 78.6 ± 62.9, K2 4.2 ± 9.3, P1 5.0 ± 7.8, P2 10.0 ± 13.6 and P3 14.8 ± 13.5. The mean duration on the closed arm was K1 141.8 ± 105.0, K2 271.2 ± 33.7, P1 285.2 ± 12.9, P2 266.2 ± 32.7 and P3 261.2 ± 15.6 Kruskal-Wallis test on the open arm 0.006 (p <0.05) and 0.026 on the close arm (p <0.05). The Mann-Whitney U test found a significant difference between the K1 and K2 groups and there was no significant difference between the P1, P2, and P3 groups in the open and close arms. There was no effect of giving Lampung Robusta Coffee Bean extract on the value of Elevated Plus Maze (EPM) Anxiety Male White Rats (Rattus novergicus) Sprague dawley strain induced by Monosodium Glutamate (MSG).